CORPORATE PREPARATION OF FUTURE TEACHERS FOR EDUCATIONAL ACTIVITIES BASED ON A SYNERGETIC APPROACH (American Journal of Pedagogical and Educational Research, 2025)
This article considers the importance of preparing future teachers for their educational activities, taking into account social and cultural changes in society. The main idea of the synergistic approach is to effectively organize the pedagogical process by corporately combining the individual characteristics of the teacher and his influence on students.